Perbandingan brand equity produk sabun pembersih wajah merek ponds dengan biore pada mahasiswa fakultas keguruan dan ilmu pendidikan universitas mulawarman samarinda - Christian, Ari K.; Kuleh, J.; ZA, Saida Zainurossalamia (JURNAL MANAJEMEN, 2016)
This research aim to know the comparison of brand equity between facial wash product brand ponds with biore. Data analysistechniqueused isdifferent fromthe meantestwithpairedsamples. Based on the result of the study, it was found that difference between facial wash brand ponds with biore. Of the four indicators that make up the brand equity, ponds is superior to the biore. Additionaly the Biore expected to increase four indicator shaper brand equity in order to become a top brand of facial wash product.Keyword: Brand Equity, Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty.